2007
DOI: 10.1136/gut.2006.106666
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis staging in clinical practice: the OLGA staging system

Abstract: Background: The available classifications of gastritis are inconsistently used, possibly because none provides immediate prognostic/therapeutic information to clinicians. As histology reporting of hepatitis in terms of stage is clinically useful and widely accepted, an international group (Operative Link on Gastritis Assessment (OLGA)) proposed an equivalent staging system for reporting gastric histology. Gastritis staging integrates the atrophy score (obtained by biopsy) and the atrophy topography (achieved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
329
2
25

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(370 citation statements)
references
References 39 publications
14
329
2
25
Order By: Relevance
“…Rugge et al [35] suggested application of the Operative Link for Gastritis Assessment (OLGA) system for prediction of neoplastic progression. Ninety-three patients followed for more than 12 years by upper gastrointestinal endoscopy and serum sampling for pepsinogens and H. pylori status developed invasive or intra-epithelial neoplasia only if they have been defined as at ''high risk'' according to the OLGA staging system, at inclusion (OLGA III or IV).…”
Section: H Pylori As High Risk Indicatormentioning
confidence: 99%
“…Rugge et al [35] suggested application of the Operative Link for Gastritis Assessment (OLGA) system for prediction of neoplastic progression. Ninety-three patients followed for more than 12 years by upper gastrointestinal endoscopy and serum sampling for pepsinogens and H. pylori status developed invasive or intra-epithelial neoplasia only if they have been defined as at ''high risk'' according to the OLGA staging system, at inclusion (OLGA III or IV).…”
Section: H Pylori As High Risk Indicatormentioning
confidence: 99%
“…Even assuming that the technological progress of endoscopes and more comprehensive studies can substantially change this decision, the Consensus opted to follow the European recommendation to perform, at least, the removal of two fragments in the antrum and at least two fragments in the gastric corpus, in both small and large curvature (40) . It is also recommended that histological analysis of the fragments be made under the criteria established by the updated Sydney System (41) and, where possible, through it, to promote the atrophy and intestinal metaplasia graduation as recently described by systems, OLGA -Operative Link Assessment on Gastritis -and OLGIM -Operative Link on Gastritis by Intestinal Metaplasia (18,176) .…”
Section: -Year Interval Between Endoscopic Examinations For Patientsmentioning
confidence: 99%
“…8 The diagnosis of atrophy or IM is currently based on histology of biopsy specimens from certain anatomic locations of the gastric mucosa, i.e., the updated Sydney System 9,10 or Operative Link for Gastritis Assessment. 11,12 Updated Sydney System recommends taking at least five biopsy specimens: two from the antrum, two from the corpus and one from the incisura angularis. However, multiple biopsies and histologic examination are time-consuming procedure and may not be easy to apply in usual clinical practices.…”
Section: Atrophic Gastritis As a Pre-neoplastic Conditionmentioning
confidence: 99%